Commerce, conflict, and contamination: yellow fever in early-independence Veracruz in the US imaginary, 1821-1848 - Beau D.J. Gaitors (História, Ciências, Saúde: Manguinhos)
Abstract While commercial links between Mexico and the United States through the port city of Veracruz brought significant economic and social advantages in the early nineteenth century, public health concerns around yellow fever produced fascination and fear among US audiences (in southern and eastern port cities) from times of peace until the US invasion and occupation of Mexico (1846-1848). This article addresses the complex linkages between commerce, conflict, and contamination in reference to the port city of Veracruz and the United States in Mexico’s early decades of independence. More specifically, this article addresses the concern in early nineteenth-century US periodicals around yellow fever outbreaks and potential contamination, showing the constant presence of yellow fever in Veracruz in the US imaginary.